Performance evaluation of new plasticizers for stretch PVC films - Coltro, Leda; et al. (2013)
Six stretch PVC films have been formulated to have Shore A hardness of approx. 80 and nominal thickness of 15 mm with the aim of evaluating the performance of plasticizers from renewable and non-renewable sources for stretch PVC films intended to be employed as packaging. The reference film was produced with DEHA and ESBO, while the other films were produced with conventional plasticizers (ATBC and Polyadipate), new plasticizers from renewable sources (Mixture of glycerin acetates and Acetic acid esters of mono- and diglycerides of fatty acids) or a plasticizer employed in toy and childcare applications (DEHT) as a third plasticizer. The films were evaluated as to their physical and mechanical properties (durometer hardness, tensile strength and elongation), IR spectroscopy and light transmission. The several plasticizers influenced the mechanical properties of the PVC films to different degrees. All films will probably show adequate performance when used in packaging applications. Nevertheless, the vegetable oil-based plasticizers showed better mechanical performance than the other plasticizers when compared to DEHA.